Chaotic attractors of two-dimensional invertible maps - Vadim S. Anishchenko; Tatjana E. Vadivasova; Galina I. Strelova; Andrey S. Kopeikin (Discrete Dynamics in Nature and Society)
In this paper, we investigate the characteristics of quasihyperbolic attractors and quasiattractors in Invertible dissipative maps of the plane. The criteria which allow one to diagnose the indicated types of attractors in numerical experiments are formulated.